Ragam Hias Medalion pada Nisan-Nisan Makam di Palembang - Retno Purwanti (KALPATARU, 2021)
The Islamic tombs in Palembang date from the 16th-20th century AD. Some of the tombs in Palembang are plain and some have decorations. Ornaments are affixed to the jirat and tombstones. The ornaments found on the headstones include medallions. The medallion ornaments vary in shape and are commonly found in temple buildings in Java in the 9th-16th centuries AD. The medallion decorative motifs in Palembang are found on Islamic tombs from the time of the Palembang Darussalam Sultanate. The medallion decorative motifs found are varied and interesting to study from the similarities and differences with those in Java, as well as the reasons for the emergence of these similarities and differences. Based on these two problems, this paper aims to identify the forms of medallion decoration, similarities, and differences, as well as the background to the similarities and differences in the medallion decorations in Palembang and Java. To answer these two problems, archaeological research methods were used by describing the ornamental variety and identifying its diversity. After that, it was analyzed qualitatively using symbolic theory. The results of the study show that the similarities in the decorations are due to the historical relationship between Palembang and the Majapahit and Demak kingdoms in Java. The difference in the medallion decoration is caused by the creativity factor of Palembang artists.